The Effect of Montessori Method Implementation and Classical Learning Method on Strengthening Children's Character Education (PAUD) Using Flash Cards - Nindhi Puspita Dewi (Jurnal Indonesia Sosial Teknologi, 2024)
Education is very important for the intelligence of the nation. The education of the nation's children is referred to as one of the factors that can lead to success or setbacks for the country's future. Education in Indonesia is still not perfect, and it is not perfect to say that it has achieved progress in character education; as evidence, this time, there are still many students who have lost their sense of nationality, honesty, courtesy, and sense of responsibility. So, for that, character education absolutely must be revitalized again. This quantitative study aims to determine the effect of the differences in implementing the Montessori and Classical learning methods on strengthening character education in early childhood using flash cards. The design used in this research is in the form of a comparative quantitative approach. Questionnaires were distributed to 12 teachers from each school, with 6 teachers as respondents. The data obtained from the questionnaire distribution is then analyzed using a Likert scale, and the results of student learning scores are analyzed using an independent t-test. The research results show that the teacher's perception of implementing the Montessori Method and the Classical Learning Method towards strengthening character education using flash cards has a very effective category with an achievement of 82% for learning the Montessori Method. While the effective category with an achievement of 73% for the Classical Learning Method. Based on the Independent t-test, the value of the difference in character education shows the effect of the difference, namely 0.20. The effect of this difference is statistically categorized as not real, or there is no difference in the effect of the implementation of the Montessori Method and the Classical Learning Method on strengthening early childhood character education. The Montessori and Classical Learning Method can be good for early childhood character education.